Gramsci e il movimento per l'educazione nuova. Alcuni spunti di riflessione - Daniele Martinez (Firenze University Press, 2014)
This paper traces the considerations of Gramsci about the New Education Movement. We have analyzed the relationships between the Educational Activism and the Gramsci's work. In particular we evaluated similarities and differences with the Pragmatism of Dewey, with the Educational Spontaneism, inspired by the tradition of Rousseau, and with the Italian Neo-idealist Pedagogy represented by the figure of Lombardo Radice. In conclusion, in the history of the italian school after the Second World War, we examined the mean- ing of the position of Gramsci and Educational Activism.